2006
DOI: 10.1371/journal.ppat.0020092
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Reduces Plasma VEGF-C/sVEGFR-3 and Improves Pathology in Lymphatic Filariasis

Abstract: Lymphatic filariasis is a disease of considerable socioeconomic burden in the tropics. Presently used antifilarial drugs are able to strongly reduce transmission and will thus ultimately lower the burden of morbidity associated with the infection, however, a chemotherapeutic principle that directly induces a halt or improvement in the progression of the morbidity in already infected individuals would constitute a major lead. In search of such a more-effective drug to complement the existing ones, in an area en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
239
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(257 citation statements)
references
References 80 publications
14
239
3
1
Order By: Relevance
“…There was also a reduction in the proportion of living female and male worms at this point of time, but the number of extirpated worms was too small to allow the definite conclusion of a macrofilaricidal effect. However, a macrofilaricidal activity of doxycycline was demonstrated against Wuchereria bancrofti (Taylor et al 2005;Debrah et al 2006b), and recently also against O. volvulus, albeit at a higher daily dose of 200 mg/day, also after a longer observation period .…”
Section: Introductionmentioning
confidence: 98%
“…There was also a reduction in the proportion of living female and male worms at this point of time, but the number of extirpated worms was too small to allow the definite conclusion of a macrofilaricidal effect. However, a macrofilaricidal activity of doxycycline was demonstrated against Wuchereria bancrofti (Taylor et al 2005;Debrah et al 2006b), and recently also against O. volvulus, albeit at a higher daily dose of 200 mg/day, also after a longer observation period .…”
Section: Introductionmentioning
confidence: 98%
“…Besides an adulticidal effect, doxycycline has recently been shown to ameliorate pathology in patients with bancroftian filariasis, such as dilation in supratesticular scrotal lymphatic vessels, lymphedema, and hydrocele. 9 This effect was previously unknown and has not been observed after DEC; rather, in contrast, transient hydroceles developed and pre-existing ones increased after DEC. 3 We therefore addressed the following parameters in this trial: 1) long-term antimicrofilarial activity (caused by sterilization of adult female worms); 2) depletion of Wolbachia ; 3) loss of worm nests; 4) reduction of antigen levels; and 5) amelioration of dilated scrotal lymphatic vessels.…”
Section: Discussionmentioning
confidence: 94%
“…Although it requires a longer treatment time than currently used drugs, the advantage of anti-wolbachial treatment is that it has shown higher macrofilaricidal activity than DEC (ivermectin is not macrofilaricidal on its own) and that it leads to a reduction of lymph vessel dilation as well as to an improvement of lymphedema stages 9,15,16 and also hydrocele. 17 Because the treatment time (4 weeks) with just doxycycline needed to achieve a macrofilaricidal effect is long, the macrofilaricidal efficacy of doxycycline treatment before DEC treatment was tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF) family members have also been implicated in lymphangiogenesis. It was recently shown that lymphaticendothelial specific VEGF-C levels are significantly elevated in individuals with filarial disease (68). The other VEGF family member that has been implicated to play a role in filarial disease is VEGF-A (69).…”
Section: Pathogenesis Of Filarial Diseasementioning
confidence: 99%